A new species of the Neotropical spittlebug genus Catrimania Fennah, 1968 (Hemiptera: Cercopidae) with a dichotomous key to species of the genus - Carvalho, Gervásio Silva; Paladini, Andressa (Zootaxa, 2017)
A new species of the Neotropical spittlebug genus Catrimania Fennah from Ecuador, C. tiobino sp. nov., is described. A dichotomous key to species of the genus is provided.